2021
DOI: 10.1242/bio.057398
|View full text |Cite
|
Sign up to set email alerts
|

A Caenorhabditis elegans behavioral assay distinguishes early stage prostate cancer patient urine from controls

Abstract: Current methods for non-invasive prostate cancer (PrCa) detection have a high false-positive rate and often result in unnecessary biopsies. Previous work has suggested that urinary volatile organic compound (VOC) biomarkers may be able to distinguish PrCa cases from benign disease. The behavior of the nematode Caenorhabditis elegans has been proposed as a tool to take advantage of these potential VOC profiles. To test the ability of C. elegans Bristol N2 to distinguish PrCa cases from controls, we performed ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…By using the PASS method, the olfactory system of C. elegans that might accurately sense odors at far lower concentrations than previously known will be investigated in the near future. Furthermore, this method can be applied to any technology and it can be utilized in various industrial fields, such as medicine and medical care [ 33 , 34 , 35 , 36 ], life sciences, veterinary medicine, agriculture and forestry, food, quantum science, and environmental fields.…”
Section: Discussionmentioning
confidence: 99%
“…By using the PASS method, the olfactory system of C. elegans that might accurately sense odors at far lower concentrations than previously known will be investigated in the near future. Furthermore, this method can be applied to any technology and it can be utilized in various industrial fields, such as medicine and medical care [ 33 , 34 , 35 , 36 ], life sciences, veterinary medicine, agriculture and forestry, food, quantum science, and environmental fields.…”
Section: Discussionmentioning
confidence: 99%
“…Further diagnosis and monitoring of symptoms is necessary to confirm the presence of cancer and its type. In addition, it has previously been shown that attractive VOCs are present in the urine during both early and late stages of cancer (20,22), so it is likely that in future assays, we can demonstrate the ability to screen for cancer at the earliest stages.…”
Section: Discussionmentioning
confidence: 99%
“…Study to accurately identify urine samples from canine cancer patients (Figure 1). Previous chemotaxis assays have used anywhere from three to six replicates to determine the mean CI (20)(21)(22). For canine urine assays, we often found variance in the response and magnitude in individual replicates within an assay (Supplementary Table 1).…”
Section: Developing the Acd Test To Distinguish Cancer And Non-cancer...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, given that the Ras-MAPK pathway regulates meiosis and spout formation in C. elegans , such a pathway has been shown to reduce chemotaxis to odorants, and the exposure of the odorant isoamyl alcohol to C. elegans resulted in the activation of the MAP kinase in olfactory neurons within 10 s, suggesting that the Ras-MAPK pathway may be a candidate pathway involved in scent detection using C. elegans , although the underlying mechanisms for chemotaxis remain to be elucidated [ 13 , 14 , 32 , 33 ]. Eventually, recent study proposed that 2-octonone and pentanal levels were increased in urine of prostate cancer patients, compared to healthy controls, suggesting that both 2-octonone and pentanal higher levels in urine may be biomarkers of prostate cancer [ 34 ]. Moreover, very recent study of pancreatic ductal adenocarcinoma indicated that possible VOCs and metabolite biomarkers in urine were acetone, 2-pantanone, 4-methyl-2-heptanone, D-limonene, and levomenthol, though both chronic pancreatitis and PDAC shared common VOCs, so in the previous study, the authors could not fully discriminate both chronic pancreatitis and PDAC using GC-TOF-MS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%